Dampak Pengelolaan Keuangan atas Literasi Keuangan, Gaya Hidup dan Gender Mahasiswa Akuntansi di Masa Transisi Covid-19 - Mochamad Apriadi Rachmawan Putra; Fajar Syaiful Akbar (Journal of Management and Bussines (JOMB), 2023)
This study aims to examine the effect of Financial Literacy, Lifestyle and Gender on Financial Management of Accounting Students during the Covid-19 Transition Period. The research method used in this research is quantitative and the type of data used in this research is primary data with a data collection method in the form of a questionnaire. The results of the research show that Financial Literacy has an effect on Financial Management, Lifestyle has an effect on Financial Management and Gender has an effect on Financial Management. In conclusion, that understanding in managing and managing finances has an impact on shaping student financial management. Keywords : Financial Literacy, Lifestyle, Gender, Financial Management